Tantangan Pembelajaran Daring di Era Pandemi - Musfira Musfira (2021)
The Indonesian government through President Jokowi issued a Large-Scale Social Restriction Policy (PSBB) to prevent the spread of the Covid-19 virus, which also had an impact on changing face-to-face learning with online or online learning methods. Learning is a process that is not only a transfer of knowledge, but an active process of seeking knowledge or the process of formulating knowledge. Learning is a complex system whose success can be seen from two aspects, namely the production aspect and the process aspect. Therefore, a reciprocal interaction is needed from a process that involves teachers, learners and learning materials, one of which is to develop and improve the ability to interact and communicate to produce an effective learning process. Learning should be oriented towards learning as individuals who have potential, abilities, interests, motivations that can be explored and developed through the learning process. Because, learning resources are not only centered on the teacher but also an environment oriented to broad-based learning by utilizing technological instruments as learning aids (as a tool) that supports learning to accelerate and expand learner's knowledge and information.